Study on the reduction method of the satellite thermal mathematical model. (June 2017) - Kim, Jung Hoon; Kim, Byoungsoo
Highlights: Proposing a thermal model reduction algorithm for non-symmetric full matrices manipulation. Performance of the multi-thread computing architecture for model reduction. Evaluating the quality of the reduced model with isothermal meshing tolerances. Abstract: The thermal model reduction method is introduced to condense a huge satellite panel thermal model into a simplified model in order to make efficient calculations in the thermal analysis of a satellite in orbit. The static condensation algorithm with a substitution matrix manipulation is employed to handle the huge matrices without any numerical restriction. The relevant mathematical procedures of reduction are described step-by-step. The thermal model example of a satellite panel is illustrated to demonstrate the developed reduction method and its results are discussed. The influence of generated meshes for the reduced thermal model is reviewed. The calculation times are assessed and comparison between the developed method and the classical block-form LU decomposition method is also performed.